P022 Pathologic involvement of the farnesoid X receptor/fibroblast growth factor 19 axis to the Crohn's disease early postsurgical recurrence. (27th May 2021) - Suau, R; Garcia-Jaraquemada, A; Lorén, V; Torres, P; Jou, E; Llaves, M; Aterido, A; Julià, T; Zabana, Y; Lozano, J J; Domènech, E; Mañosa, M; et al.
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory bowel disease that normally requires bowel surgical resection due to intra-abdominal inflammatory complications such as fistulae and stenosis. However, 90% of patients that underwent surgery and did not receive prophylaxis, suffer from postsurgical endoscopic recurrence within one year. Methods: The objective of this study is to understand the de novo postsurgical lesion formation in order to stablish a potential mechanism of action and its derived predictive signals to devise preventive strategies. To achieve it, transcriptome analyses of the inflamed and macroscopically unaffected zone of the ileocecal resection from 20 patients from a hospital cohort and 10 controls were performed. Patients were classified for early postsurgical recurrence by means of Rutgeerts index (i0<i1<i2<i3<i4) and transcriptome was analysed using different comparatives and clustering strategies. In order to replicate the results from the transcriptome analyses, the statistically significant genes and rationally related genes have been tested by qPCR in a corroboration cohort formed by 24 different patients. Results: The transcriptome results showed there were no differences neither between i0, i1 and i2a (anastomotic lesions) nor when comparing i2b (non-anastomotic lesions) vs ≥i3. However, when comparing i0+i1+i2a vs. i2b+i3+i4 there were differently expressed genes highlighting ADIPOQ in the inflamed zone and the FXR/FGF19 axis in the unaffected zone. When replicating the results in the corroborative cohort, we identified FXR and other xenobiotic nuclear receptors as the genes differentially expressed in i2a vs i2b, i3 and/or i4, mainly in the macroscopically unaffected zone. Specifically, the differentially expressed genes were: MOGAT2, PXR, FXR and AHR (i2a vs i4), PPARα and FXR (i2a vs i3), TMIGD1, PPARα, FXR and AHR (i2a vs i3+i4) and FXR (i2a vs i2b+i3+i4). Conclusion: Nuclear receptor FXR is activated in the ileum by bile acids action and it is key in the lipid metabolism regulation and in the bile acids production by means of FGF19. Moreover, ileal FXR, as well as other xenobiotic nuclear receptors, actively participates in the enhancement of the intestinal barrier function and in the innate immunity regulation. In conclusion, the results obtained in this study suggest a link between bowel xenobiotic metabolism and the de novo lesion formation in previously unaffected areas in the postsurgical recurrence in CD.